OPTIMALISASI KEPEMIMPINAN NASIONAL DALAM MELAKSANAKAN KEBIJAKAN DISTRIBUSI PANGAN DAPAT MEWUJUDKAN KETAHANAN PANGAN NASIONAL - Arditya Wicaksono (Agriekonomika, 2012)
ABSTRACTConversion of agricultural land should be prevented from governments and national leaders. Regulations prohibiting the conversion of agricultural land should be consistent with the commitment reinforced with evidence. Rehabilitation Program and the Agricultural Land Utilization Optimization can be implemented through a variety of strategic programs along with the optimization of the technology evolve over time. Coordination among relevant institutions is absolutely necessary for the achievement of synergy, synchronicity in national food securityKeywords: national leaders, regulatoryandpolicysynergy